PHYLOGENETIC RELATIONSHIPS AMONGST 10 Durio SPECIES BASED ON PCR-RFLP ANALYSIS OF TWO CHLOROPLAST GENES - Santoso, Panca J.; Saleh, Ghizan B.; Saleh, Norihan M.; Napis, Suhaimi (Indonesian Agency for Agricultural Research and Development - MOA, 2005)
Twenty seven species of Durio have been identified in Sabah and Sarawak, Malaysia, but their relationships have not been studied. This study was conducted to analyse phylogenetic relationships amongst 10 Durio species in Malaysia using PCR-RFLP on two chloroplast DNA genes, i.e. ndhC-trnV and rbcL. DNAs were extracted from young leaves of 11 accessions from 10 Durio species collected from the Tenom Agriculture Research Station,Sabah, and University Agriculture Park, Universiti Putra Malaysia. Two pairs of oligonucleotide primers, N1-N2 and rbcL1-rbcL2, were used to flank the target regions ndhC-trnV and rbcL. Eight restriction enzymes, HindIII, BsuRI, PstI, TaqI, MspI, SmaI, BshNI, and EcoR130I, were used to digest the amplicons. Based on the results of PCR-RFLP on ndhC-trnV gene, the 10 Durio species were grouped into five distinct clusters, and theÂ accessions generally showed high variations. However, based on the results of PCR-RFLP on the rbcL gene, the species were grouped into three distinct clusters, and generally showed low variations. This means that ndhC-trnV gene is more reliable for phylogenetic analysis in lower taxonomic level of Durio species or for diversity analysis, while rbcL gene is reliable marker for phylogenetic analysis at higher taxonomic level. PCR-RFLP on the ndhC-trnV and rbcL genes could therefore be considered as useful markers to phylogenetic analysis amongst Durio species. These finding might be used for further molecular marker assisted in Durio breeding program.